Advancements and prospects of novel biologicals for myasthenia gravis: toward personalized treatment based on autoantibody specificities - Ma, Chi; Liu, Dan; Wang, Benqiao; Yang, Yingying; Zhu, Ruixia (Frontiers in Pharmacology, 2024)
Myasthenia gravis (MG) is an antibody-mediated autoimmune disease with an prevalence of 150-250 cases per million population. Autoantibodies include long-lived antibodies against acetylcholine receptor (AChR), mainly of the IgG1 subclass, and IgG4, produced almost exclusively by short-lived plasmablasts, which are prevalent in muscle-specific tyrosine kinase (MuSK) myasthenia gravis. Numerous investigations have demonstrated that MG patients receiving conventional medication today still do not possess satisfactory symptom control, indicating a substantial disease burden. Subsequently, based on the type of autoantibody and the pathogenesis, we synthesized the published material to date and reached a conclusion regarding the literature related to personalized targeted therapy for MG. Novel agents for AChR MG have shown their efficacy in clinical research, such as complement inhibitors, FcRn receptor antagonists, and B-cell activating factor (BAFF) inhibitors. Rituximab, a representative drug of anti-CD20 therapy, has demonstrated benefit in treating MuSK MG patients. Due to the existence of low affinity antibodies or unidentified antibodies that are inaccessible by existing methods, the treatment for seronegative MG remains complicated, thus special testing and therapy considerations are necessary. It may be advantageous to initiate novel biologicals application at an early stage of disease. Currently, therapies can also be combined and individualized according to different types of antibodies.With such a wide range of drugs, how to tailor treatment strategies to patients with various conditions and find the most suitable solution for each MG profile are our necessary and urgent aims.This article briefly introduces the pathogenic mechanisms of myasthenia gravis and current treatments. From the perspective of different categories of autoantibodies, the mechanism of action of today's latest targeted drugs is explained.